Targeting EIF3C to suppress the development and progression of nasopharyngeal carcinoma - Zhao, Qian; Luo, Xuehui; Li, Honghui; Bai, Yanxia; Chen, Qian; Yang, Ming; Pei, Bei; Xu, Chongwen; Han, Suxia (Frontiers in Bioengineering and Biotechnology, 2022)
Nasopharyngeal carcinoma occurs in many parts of the pars nasalis pharyngis, and the pathological type is mainly squamous cell carcinoma. Because of the special position of nasopharynx, breathing, pronunciation and daily life will be seriously affected. At present, the research direction of nasopharyngeal carcinoma is mainly to explore the law of tumor cell proliferation and migration, study the molecular mechanism, master its biological behavior and clinical significance, try to find therapeutic targets, and further improve the level of tumor treatment. However, the pathologic structure and molecular mechanism of nasopharyngeal carcinoma have not been fully elucidated. In this study, the Lentivirus-mediated EIF3C shRNA vector (L.V-shEIF3C) was constructed to down-regulate the expression of EIF3C in human pharyngeal squamous carcinoma cell FaDu and the human nasopharyngeal carcinoma cell 5-8F, it was found that down-regulation of EIF3C could significantly inhibit the cell proliferation, promote cell apoptosis, induce cell cycle arrest, and inhibit the formation and growth of tumors in mouse models. This study provides strong evidence that EIF3C is a key gene driving the development and progression of head and neck cancer, which is of great significance for the diagnosis, prognosis or treatment of tumors, suggesting that EIF3C may become a valuable therapeutic development and intervention target.